Fourteen-year trends in the criminal justice response to child sexual abuse reports in New South Wales - Cashmore, Judith (Child maltreatment, 2020)
This study of attrition compares the prosecution of child sexual offenses reported while the complainant was still a child with those in which the report was delayed into adulthood; it also compares matters involving adult and young (under 18 years) suspects/defendants. It is based on an analysis of police and court administrative data in New South Wales, Australia over a 14-year period (2003?2016). Only one in five (21.6%) proceeded beyond the investigation stage. Criminal proceedings were more likely to commence when the alleged victim was 7?12 years old at the time of the incident, when the suspect was an adult and at least 10 years older than the victim, and also when the report to police was made when the victim was an adult. Just over half (55.5%) of the matters finalized in court resulted in a conviction. Cases in the higher courts were less likely to be dismissed and more likely to feature guilty pleas and convictions at trial than cases in the lower courts. The overall estimate is that only 12% of offenses reported to police resulted in a conviction, at a relatively stable rate over 14 years. These findings are consistent with those of comparable studies.